Multilingualism in Dublin: Home Language Use Among Primary School Children, Report on a Pilot Survey - Carson, Lorna (My University, 2010)
Travellers who arrive at Dublin airport from abroad easily receive the impression that they have arrived in a bilingual country. However, whilst both English and Irish appear on official signage, the languages they frequently hear are Russian and Polish. Mac Einri and White (2008: 153) suggest that `Ireland?s historical demographic and migration profile can fairly be described as unique, at least in European terms.? Unlike its neighbours, large?scale population diversity has been a recent phenomenon in Ireland. In the 1990s, the country?s economy began to prosper (referred to as the Celtic Tiger), and contributed to a reversal of the well?trodden path of Irish emigration towards England, North America and beyond. A surge of immigrants arrived in Ireland from every continent. Newcomers ? professionals, seasonal migrant workers, asylum seekers, refugees ? along with returning Irish emigrants, created an entirely different demographic and linguistic profile in the space of a decade. Kallen (2010: 55) highlights how the `linguistic landscape in Dublin is undergoing a profound change?. This shifting city landscape is observable both in `?top?down?, official signage? (ibid: 42) in the civic domain ? where state agencies now frequently provide information in Russian, Polish, Arabic and Mandarin Chinese in addition to English and Irish ? through to prolific multilingual entrepreneurial signage, and even at the level of street detritus (ibid: 55).
PUBLISHED
Dublin: Centre for Language and Communication Studies/Tilburg, NL, Tilburg University
Keywords: Language and linguistics; Creative Arts Practice; International Integration